Highly Sensitive Electrocatalytic Determination of Formaldehyde Using a Ni/Ionic Liquid Modified Carbon Nanotube Paste Electrode - Ebrahim Zarei; Mohammad Reza Jamali; Farideh Ahmadi (Bulletin of Chemical Reaction Engineering & Catalysis, 2018)
In this study, ionic liquid 1-hexyl-3-methylimidazolium hexafluorophosphate was applied as additives to fabricate a novel ionic liquid/carbon nanotube paste electrode (IL/CNPE). This electrode was characterized by electrochemical impedance spectroscopy and cyclic voltammetry. Results showed that the electron transfer rate and reversibility of the electrode were increased by the ionic liquid. The morpho-logy of prepared IL/CNPE was studied by scanning electron microscopy. Nickel/ionic liquid modified carbon nanotube paste electrode (Ni/IL/CNPE) was also constructed by immersion of the IL/CNPE in nickel sulfate solution. Ionic liquid showed significant effect on the accumulation of nickel species on the surface of the electrode. Also, the values of electron transfer coefficient, charge-transfer rate constant and electrode surface coverage for Ni(II)/Ni(III) redox couple of the Ni/IL/CNPE were found to be 0.32 and 2.37×10-1 s-1 and 2.74×10-8 mol.cm-2, respectively. The Ni/IL/CNPE was applied successfully to highly efficient electrocatalytic oxidation of formaldehyde in alkaline medium. The effects of various factors on the efficiency of electrocatalytic oxidation of formaldehyde were optimized. Under the optimized condition, cyclic voltammetry of formaldehyde at the modified electrode exhibited two linear dynamic ranges in the concentration ranges of 7.00×10-6 to 9.60×10-5 mol.L-1 and 9.60×10-5 to 32.00×10-3 mol.L-1 with excellent detection limit of 9.50×10-7 mol.L-1 (3σ/slope), respectively. Also, the method was successfully applied for formaldehyde measurement in real sample.